Health Insurance for Cancer Care in Asia: Thailand - Pongpak Pittayapan (Asia-Pacific Journal of Oncology Nursing, 2016)
Thailand has a universal multi-payer system with two main types of health insurance: National Health Security Office or public health insurance and private insurance. National health insurance is designed for people who are not eligible to be members of any employment-based health insurance program. Although private health insurance is also available, all Thai citizens are required to be enrolled in either national health insurance or employees′ health insurance. There are many differences between the public health insurance and private insurance. Public health insurance, therefore, initiates programs that offer many sets of benefit packages for high-cost care. For cancer care, cover screening, curative treatment such as surgery, chemotherapy, radiation together with supportive and palliative care.